Stopping Hospital Infections With Environmental Services (SHINE): A Cluster-randomized Trial of Intensive Monitoring Methods for Terminal Room Cleaning on Rates of Multidrug-resistant Organisms in the Intensive Care Unit . (1st February 2022) - Ziegler, Matthew J; Babcock, Hilary H; Welbel, Sharon F; Warren, David K; Trick, William E; Tolomeo, Pam; Omorogbe, Jacqueline; Garcia, Diana; Habrock-Bach, Tracy; Donceras, Onofre; Gaynes, Steven; Cressman, Leigh; et al.
Abstract: Background: Multidrug-resistant organisms (MDROs) frequently contaminate hospital environments. We performed a multicenter, cluster-randomized, crossover trial of 2 methods for monitoring of terminal cleaning effectiveness. Methods: Six intensive care units (ICUs) at 3 medical centers received both interventions sequentially, in randomized order. Ten surfaces were surveyed each in 5 rooms weekly, after terminal cleaning, with adenosine triphosphate (ATP) monitoring or an ultraviolet fluorescent marker (UV/F). Results were delivered to environmental services staff in real time with failing surfaces recleaned. We measured monthly rates of MDRO infection or colonization, including methicillin-resistant Staphylococcus aureus, Clostridioides difficile, vancomycin-resistant Enterococcus, and MDR gram-negative bacilli (MDR-GNB) during a 12-month baseline period and sequential 6-month intervention periods, separated by a 2-month washout. Primary analysis compared only the randomized intervention periods, whereas secondary analysis included the baseline. Results: The ATP method was associated with a reduction in incidence rate of MDRO infection or colonization compared with the UV/F period (incidence rate ratio [IRR] 0.876; 95% confidence interval [CI], 0.807–0.951; P  = .002). Including the baseline period, the ATP method was associated with reduced infection with MDROs (IRR 0.924; 95% CI, 0.855–0.998; P  = .04), and MDR-GNB infection or colonization (IRR 0.856; 95% CI, 0.825–0.887; P  < .001). The UV/F intervention was not associated with a statistically significant impact on these outcomes. Room turnaround time increased by a median of 1 minute with the ATP intervention and 4.5 minutes with UV/F compared with baseline. Conclusions: Intensive monitoring of ICU terminal room cleaning with an ATP modality is associated with a reduction of MDRO infection and colonization. Abstract : We performed a multicenter, cluster-randomized, crossover trial of 2 methods for intensive monitoring of terminal cleaning effectiveness. Intensive monitoring of intensive care unit terminal room cleaning with an adenosine triphosphate modality is associated with a relative reduction of infection and colonization with multidrug-resistant organisms.